Edukasi Anti-Bullying untuk Meningkatkan keterampilan Berprilaku Positif pada SMA Negri 9 Kota Bengkulu - Putri, Dea Alesia; Abi, Yudi Irawan; Wijaya, Ermy; Ariantara, Yudi (Jurnal Gotong Royong, 2024)
The aim of carrying out this Community Service is to educate the community, especially school children, in socializing to increase understanding about bullying behavior. This Community Service is of course to provide important counseling in schools so that students can reduce criminal acts and can behave positively. Through this activity, teachers are also expected to be able to convey relevant information at school in the future. This Community Service activity 15 consists of SMA N 9. people consisting of various classes at SMA N 9 Education using the CBPR method which is carried out in a collaborative pattern. The results of this Community Service show that there was active participation from students, including 3 people who asked related questions and were able to understand what bullying and bullying are. Socialization such as education regarding bullying, sexual violence against women and children for young people, students or teenagers in the school environment is important to carry out regularly